USE OF DEVELOPING EDUCATIONAL TECHNOLOGIES IN STUDYING THE HISTORY OF PEOPLE'S MOVEMENT AGAINST RUSSIAN RULE IN TURKESTAN - Khaliyeva , Shahnoza (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This article developer education from technologies of use importance open given . Also history in their classes this education from technologies use according to recommendations working released